Entrepreneur Human Capital Inputs and Small Business Longevity - Bates, Timothy (The Review of Economics and Statistics, 1990)
Small business longevity is investigated utilizing a nationwide random sample of males who entered self-employment between 1976 and 1982. Highly educated entrepreneurs are most likely to create firms that remained in operation through 1986. Owner educational background, further, is a major determinant of the financial capital structure of small business startups. Financial capital endogeneity notwithstanding, firms with the larger financial investments at startup are consistently overrepresented in the survivor column. Firm leverage, finally, is trivial for delineating active from discontinued businesses. Reliance upon debt capital to finance business startup is clearly not associated with heightened risk of failure. Copyright 1990 by MIT Press.